2001
DOI: 10.1176/appi.ajp.158.11.1891
|View full text |Cite
|
Sign up to set email alerts
|

Familiality and Heritability of Subtypes of Attention Deficit Hyperactivity Disorder in a Population Sample of Adolescent Female Twins

Abstract: Unlike DSM-IV subtypes of ADHD, latent-class ADHD subtypes appear to be independently transmitted in families. These classes may be more appropriate targets for molecular genetic studies of ADHD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
161
5
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 166 publications
(175 citation statements)
references
References 18 publications
8
161
5
1
Order By: Relevance
“…One study 51 found no evidence of familial distinction between subtypes, a finding supported by analyses both of sibling pairs collected for a molecular genetic study 52 and of a twin sample. 53 In contrast, some twin studies based on general population samples [54][55][56] have found distinct genetic (and environmental) influences on the different subtype symptom scores.…”
Section: Reading Disabilitymentioning
confidence: 97%
See 1 more Smart Citation
“…One study 51 found no evidence of familial distinction between subtypes, a finding supported by analyses both of sibling pairs collected for a molecular genetic study 52 and of a twin sample. 53 In contrast, some twin studies based on general population samples [54][55][56] have found distinct genetic (and environmental) influences on the different subtype symptom scores.…”
Section: Reading Disabilitymentioning
confidence: 97%
“…60,61 The latent classes so defined are familial, heritable and unlike the DSM-IV subtypes are more consistently reported to be independently transmitted. 53,56 Molecular genetic studies based on these classes have so far yielded negative findings apart from a reported significant association between the severely inattentive subtype and a variant within the nicotinic acetylcholine receptor alpha 4 subunit gene (CHRNA4). 62 One problem is that latent class genetic findings could be difficult to replicate if class structures vary in different types of populations.…”
Section: Reading Disabilitymentioning
confidence: 99%
“…Some research evidence suggests heterogeneity at several levels: phenotypic [e. g., 16], neuropsychological [e. g., 150], psychophysiological [e. g., 7,23,125], and genetic [e. g., 107,175,186]. There may be multiple developmental pathways from aetiological factors to behavioural symptoms [151,152].…”
Section: Influences On Pathogenesismentioning
confidence: 99%
“…This hypothesis is supported by other research groups that reported familial clustering of latent class and DSM-IV defined ADHD subtypes. [80][81][82][83] In addition, different candidate genes, such as 5HT1B or SLC4A3, have been associated with specific ADHD diagnostic groups. 84,85 In this respect, the combined subtype may represent a distinctive and more homogeneous phenotype that could facilitate the identification of genetic factors contributing to ADHD.…”
Section: Ht2amentioning
confidence: 99%